2020
DOI: 10.3390/su12177067
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Implications of COVID-19 in California

Abstract: The COVID-19 pandemic has significantly affected human health and the economy. The implementation of social distancing practices to combat the virus spread, however, has led to a notable improvement in air quality. This study compared the surface air quality monitoring data from the United States Environmental Protection Agency (U.S. EPA)’s AirNow network during the period 20 March–5 May in 2020 to those in 2015–2019 from the Air Quality System (AQS) network over the state of California. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…Similar findings, i.e., reduced PM 2.5 and NO 2 concentrations, are also reported for China (e.g., Chu et al, 2021;Le et al, 2020;Liu et al, 2020;Marlier et al, 2020;Shi and Brasseur, 2020;Miyazaki et al, 2020b), India (e.g., Pathakoti et al, 2020;Sharma et al, 2020), and Europe (e.g., Chen et al, 2020;Menut et al, 2020;Sicard et al, 2020;Ordóñez et al, 2020) based on surface and/or satellite observations. For O 3 , the concentrations either increased or slightly decreased during the pandemic, depending on the region (Bekbulat et al, 2020;Huang et al, 2021;Pan et al, 2020;Zhao et al, 2020). Most of the above studies, however, are limited to comparing observations with and without lockdown measures, which correspond to different time periods under different meteorological conditions.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar findings, i.e., reduced PM 2.5 and NO 2 concentrations, are also reported for China (e.g., Chu et al, 2021;Le et al, 2020;Liu et al, 2020;Marlier et al, 2020;Shi and Brasseur, 2020;Miyazaki et al, 2020b), India (e.g., Pathakoti et al, 2020;Sharma et al, 2020), and Europe (e.g., Chen et al, 2020;Menut et al, 2020;Sicard et al, 2020;Ordóñez et al, 2020) based on surface and/or satellite observations. For O 3 , the concentrations either increased or slightly decreased during the pandemic, depending on the region (Bekbulat et al, 2020;Huang et al, 2021;Pan et al, 2020;Zhao et al, 2020). Most of the above studies, however, are limited to comparing observations with and without lockdown measures, which correspond to different time periods under different meteorological conditions.…”
Section: Introductionsupporting
confidence: 77%
“…For example, Archer et al (2020) compared the observed concentrations at all available ground monitoring sites in the US between April 2020 and the prior 5 years (2015)(2016)(2017)(2018)(2019) and found statistically significant decreases in NO 2 concentrations at more than 65 % of the monitoring sites, with an average drop of 2 ppb. Pan et al (2020) compared the surface air quality monitoring data in California during the period 20 March-5 May 2020 with those in 2015-2019 and found that PM 2.5 in 2020 exhibited a notable decrease, which could result from emission reductions associated with the COVID-19 lockdown. Similar findings, i.e., reduced PM 2.5 and NO 2 concentrations, are also reported for China (e.g., Chu et al, 2021;Le et al, 2020;Liu et al, 2020;Marlier et al, 2020;Shi and Brasseur, 2020;Miyazaki et al, 2020b), India (e.g., Pathakoti et al, 2020;Sharma et al, 2020), and Europe (e.g., Chen et al, 2020;Menut et al, 2020;Sicard et al, 2020;Ordóñez et al, 2020) based on surface and/or satellite observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil: (Dantas et al, 2020;Krecl et al, 2020;Nakada and Urban, 2020;Siciliano et al, 2020a) Other: (Mendez-Espinosa et al, 2020;Pacheco et al, 2020;Zalakeviciute et al, 2020;Zambrano-Monserrate and Ruano, 2020) Europe Multiple countries: (Baldasano, 2020;Collivignarelli et al, 2020;Filippini et al, 2020;Gautam, 2020a;Giani et al, 2020;Gualtieri et al, 2020;Higham et al, 2020;Ljubenkov et al, 2020;Sicard et al, 2020;Tobías et al, 2020;Martorell-Marugán et al, 2021) Oceania Australia: (Fu et al, 2020) New Zealand: (Patel et al, 2020) Africa Morocco: (Ass et al, 2020;Otmani et al, 2020) This includes the "discussed but not corrected" and "not discussed or corrected" categories in Figure 2. (Zheng et al, 2020), and Tianjin (Dai et al, 2020), China.…”
Section: Southeast Asiamentioning
confidence: 99%
“…15 Of note, a separate study, that confirmed reductions in ozone (O 3 ) and PM 2.5 in California (USA), has estimated thousands of air pollution-related premature deaths prevented annually in California, due to an assumed persistence of the ongoing air quality improvement. 16 Therefore, it becomes obvious that the improvement of the urban air quality can be easily controlled by simple interventions, and proper traffic management. Remote-working, since it drastically reduces the number of vehicles moving in the cities, may serve as an indirect traffic management control measure.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%